Application of industrialised building system in school project in Malaysia: the challenge - Mohd. Aizad, Johari (2013)
Industrialised Building System (IBS) is a system that used prefabricated components manufactured in the factory using highly skilled workers and heavy machinery. This method is effective to reduce the number of unskilled workers at construction sites as well as to solve some of the problems associated with construction projects such as lowering the cost of construction projects, shorten the construction time, creating a construction site clean and safe. There are five types of IBS used in this country which is pre-cast concrete framing, panel and box systems, steel formwork, steel framing, prefabricated timber framing and block work systems. Undoubtedly, IBS will provide many advantages compared to conventional method which is still widely used at present time, the IBS can drive construction industry towards global competitiveness of the country in line with productivity, quality and safety. This study focus to review the usage of IBS in the construction industry among the practitioners and its implementation in school construction projects in this country. Research is carried out by performing surveys using questionnaire and interview methods to obtain all the information. The study involved 10 construction companies in the area of Kuala Lumpur and Kuantan. In addition, information is also available from Journals, reading books and pamphlets. The findings indicate majority of professionals involved in the industry recognize that IBS is able to provide many advantages compared to conventional methods but they do not apply in their work. However, the level of acceptance of this product is very good in IBS.